0108 Insufficient Sleep Alters After-Dinner Consumption of High-Carbohydrate Snacks. (12th April 2019) - Withrow, Dana; Depner, Christopher M; Markwald, Rachel R; Melanson, Edward L; Perreault, Leigh; Eckel, Robert H; Higgins, Janine; Wright, Kenneth P
Abstract: Introduction: Understanding mechanisms underlying the relationship between insufficient sleep and weight gain has importance for public health. Our previous findings showed, although total energy expenditure is higher during insufficient sleep, food intake especially after-dinner snacks, increases beyond the elevation in energy expenditure resulting in positive energy balance and weight gain. Prior findings from other laboratories have shown that, during insufficient sleep, people select either salty and/or high-carbohydrate snacks. To better understand food choices during insufficient sleep, we examined the number of times subjects selected high-fat and high-carbohydrate snacks, and total calories consumed from after-dinner snacks during experimental sleep restriction. Methods: Sixteen healthy subjects (8F 22±5 yrs) completed a randomized cross-over inpatient protocol including 3 baseline days (9h sleep opportunity per night), followed by 5 days of insufficient (5h sleep opportunity) and 5 days of adequate (9h sleep opportunity). A variety of food items were offered ad libitum as after-dinner snacks and were weighed pre- and post-consumption. Data were analyzed using mixed model ANOVA with subject as a random factor, and condition and condition order as fixed factors. Results: Subjects consumed more calories (p=0.017) as ad libitum after-dinner snacks in the 5h insufficient sleep condition. There was no difference in the choice of snacks selected between conditions (p=0.24), but the number of times subjects selected a high carbohydrate snack (p<0.001) and the total calories consumed from high-carbohydrate snacks (p=0.004) was higher during insufficient sleep. Conversely, the consumption of high-fat snacks, the number of times subjects selected a high-fat snack, and the total calories consumed from high-fat snacks were similar between conditions (all p>0.23). Conclusion: Selection of high-carbohydrate after-dinner snacks promotes the positive energy imbalance observed during insufficient sleep. Support (If Any): NIH-R01 HL109706, NIH-UL1 TR001082, Office of Naval Research MURI (N00014-15-1-2809), Howard Hughes Medical Institute in collaboration with the Biological Sciences Initiative and Undergraduate Research Opportunities Program at the University of Colorado, Boulder, CO.